A pilot study examining injuries in elite gaelic footballers. Issue 2 (1st April 2000) - Cromwell, F; Walsh, J; Gormley, J
Abstract : Objectives —To quantify injuries in elite gaelic footballers and to determine the nature, sites, and outcome of injuries and the possible risk factors involved. Methods —Information on injuries was collected from six elite gaelic football teams by a questionnaire. The footballers were asked to recall injuries over the preceding six month period. Results —A total of 88 out of 107 subjects sustained injuries over the study period. Ninety five injuries were recorded, giving an incidence rate of 1.78 injuries per subject per year, of which 35% were recurring. It was found that 35% of injuries were sustained during training sessions. Lower body injuries predominated (77%), the ankle being the most commonly injured anatomic site. Most injuries were soft tissue in nature: muscle, 33%; ligament, 32%; tendon, 16%. The most common situations giving rise to injuries were collision (22%) and twist/turn (19%). Foul play only accounted for about 6% of injuries. Mean time off play as a result of injury was 17.3 days, and hospital admission was necessary for 15% of the injuries. Conclusion —Despite the limitations of a retrospective of this nature, the study provides useful and important information on injuries in gaelic footballers.